2021
DOI: 10.1055/a-1498-7098
|View full text |Cite
|
Sign up to set email alerts
|

A GLP-1 Receptor Agonist Inhibits Aldosterone Release in Healthy Volunteers

Abstract: Glucagon-like peptide 1 receptor agonists (GLP-1 RAs) are antidiabetic drugs with effects beyond antihyperglycemic action. The aim of the study was to examine whether a single dose of exenatide could be used as a stimulation test for the pituitary-adrenal axis. We carried out a single-group, open-label pilot clinical trial in an ambulatory setting. Ten healthy volunteers of both sexes with body weight>65 kg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Although data from literature indicate that GLP-1 inhibits ANG II action, its effect on aldosterone is less established. Baretic et al (92) and more recently Heinla et al (68) reported that a single GLP-1 infusion decreased aldosterone levels in healthy, normal weight subjects. Conversely, both Skov et al (65) and Asmar et al (66) did not find changes in aldosterone concentrations under comparable conditions.…”
Section: Effects Of Glp-1 Receptor Agonists On Raasmentioning
confidence: 97%
See 2 more Smart Citations
“…Although data from literature indicate that GLP-1 inhibits ANG II action, its effect on aldosterone is less established. Baretic et al (92) and more recently Heinla et al (68) reported that a single GLP-1 infusion decreased aldosterone levels in healthy, normal weight subjects. Conversely, both Skov et al (65) and Asmar et al (66) did not find changes in aldosterone concentrations under comparable conditions.…”
Section: Effects Of Glp-1 Receptor Agonists On Raasmentioning
confidence: 97%
“…( 92 ) and more recently Heinla et al. ( 68 ) reported that a single GLP-1 infusion decreased aldosterone levels in healthy, normal weight subjects. Conversely, both Skov et al.…”
Section: Effects Of Glp-1 Receptor Agonists On Raasmentioning
confidence: 97%
See 1 more Smart Citation
“…However, other pathways that GLP-1RAs could affect renal hemodynamics should be considered in interpreting our results. For example, clinical evidence suggests that GLP-1RA might counteract angiotensin II activity (RAAS) 54,55 , which is a sign of renoprotection against diabetic nephropathy 56 . Plus, certain neural and metabolic pathways are also thought to be involved in GLP-1RA-induced renal hemodynamic changes 57 .…”
Section: Discussionmentioning
confidence: 99%
“…As regards the endocrinal effects, despite the shortage of information on the clinical effects of GLP-1/GLP-1RAs on the hypothalamic–pituitary–ovarian hormones, experimental studies have demonstrated a potent effect of GLP-1RAs on regulating the hypothalamic–pituitary–adrenal axis. GLP-1RAs can suppress aldosterone production, which may improve fluid retention in the premenstrual phase [ 141 ]. In rats, GLP-1RAs also exhibited a positive impact on estradiol and progesterone levels along the estrous cycle [ 142 ].…”
Section: Anti-diabetic Drugs and Pmsmentioning
confidence: 99%